Improving The Quality of Life of Diabetes Mellitus Patients Through Education on Tips for Being Friendly with Diabetes Mellitus Using Audiovisual Media - Arif Hidayatullah (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
Diabetes mellitus is a chronic condition that occurs when the pancreas cannot produce enough insulin to regulate metabolism. Diabetes mellitus cannot be cured, but with good management it can prevent organ damage and failure. Diabetes mellitus has an impact on several aspects, namely: physical health aspects, psychological aspects, social aspects and environmental aspects. The aim of this research is to determine the effect of education on diabetes-friendly tips using audio-visual media on changes in the quality of life of diabetes mellitus patients. This research method is quasi-experimental. A total of 86 diabetes mellitus patients recorded in Abadijaya Village, Sukmajaya District, Depok were selected using a purposive sampling technique. The results showed that the mean value of quality of life for the audio-visual media group before was 62.26 with SD 17.583 and after 70.26 with SD 16.441. Meanwhile, the mean value of quality of life for the leaflet group before was 61.60 with SD 19.336 and after 62.21 with SD 18.252. The results of statistical tests using the independent t-test showed that the difference in quality of life scores after being given treatment between the intervention group and the control group was p value 0.035 (<0.05). There is a significant influence between education on diabetes-friendly tips using audio-visual media compared to diabetes management education using leaflets in improving the quality of life of diabetes mellitus patients. It is hoped that this research can make educational videos on tips for being friendly with diabetes mellitus as a nursing intervention standard for patients with diabetes mellitus.